Associations of intrahousehold allocation of animal source food with mother and child nutrition outcomes in low-income informal settlements of Nairobi, Kenya - Boncyk, M.; Blake, C.E.; Lepine, A.; Prieto-Merino, D.; Bukachi, S.A.; Ngutu, M.; Kadiyala, S.; Domínguez Salas, Paula (2024)
Objectives: Determine if intrahousehold animal source foods (ASF) prioritization and allocation are associated with ASF intake and nutritional outcomes in low-income informal settlements.